Tourism SME’s Competitive Advantages through ICT Based Community : The Role of GenPI in Eastern Indonesia - Yerik Afrianto Singgalen; Marthen Timisela (Journal of Indonesian Tourism and Development Studies, 2021)
This article aims to describe the role of the tourism community in the utilization of ICT to market regional tourism destinations integrated with an increasing competitive advantage in Tourism SMEs. The perspective used is Community-Based Tourism Marketing (CBTM) and Resource-Based View (RBv) in the context of Collaborative Advantages (CA) towards the relationship of the tourism community with the regional tourism industry. This study was done in a qualitative manner using a case study approach. The data was collected through in-depth interviews, observation, and document studies. The regional tourism industry had a sustainable competitive advantage in terms of activities and resource profiles such as asset ownership, capabilities, and dynamic capabilities. This finding states that the regional tourism community at the district and provincial level encouraged the competitive advantage of the regional tourism industry through intensification of marketing the tourism industry products in advantageous collaborations.Keywords: Competitive Advantages, Eastern Indonesia, GenPi Community, ICT, Resource-Based View, Tourism SME.